2015
DOI: 10.1038/jcbfm.2014.239
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cells Promote Blood Brain Barrier Breakdown and Neutrophil Infiltration in a Mouse Model of Focal Cerebral Ischemia

Abstract: Blood brain barrier (BBB) breakdown and neuroinflammation are key events in ischemic stroke morbidity and mortality. The present study investigated the effects of mast cell deficiency and stabilization on BBB breakdown and neutrophil infiltration in mice after transient middle cerebral artery occlusion (tMCAo). Adult male C57BL6/J wild type (WT) and mast cell-deficient (C57BL6/J Kit(Wsh/Wsh) (Wsh)) mice underwent tMCAo and BBB breakdown, brain edema and neutrophil infiltration were examined after 4 hours of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
72
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(72 citation statements)
references
References 40 publications
0
72
0
Order By: Relevance
“…[11] During the first few hours, neutrophils penetrate into the hypoxemic tissue which is invaded by macrophages and monocytes on consecutive days. [12] These cells are known to produce cytokines, free radicals, metalloproteinases, nitric oxide and much more. Such substances directly harm the nerve tissue, induce apoptosis and damage the blood-brain barrier.…”
Section: Discussionmentioning
confidence: 99%
“…[11] During the first few hours, neutrophils penetrate into the hypoxemic tissue which is invaded by macrophages and monocytes on consecutive days. [12] These cells are known to produce cytokines, free radicals, metalloproteinases, nitric oxide and much more. Such substances directly harm the nerve tissue, induce apoptosis and damage the blood-brain barrier.…”
Section: Discussionmentioning
confidence: 99%
“…We further report that MPP + up-regulates the expression of CD40L in Wt BMMCs co-cultured with glia/neurons in an in vitro co-culture system. Mast cells play an important role in the mechanism of BBB dysfunction, neuroinflammation and frequently co-localized next to glial cells in neuroinflammatory conditions in the brain (Seeldrayers et al, 1992; Kim et al, 2010; McKittrick et al, 2015). Previous studies have shown that intravenously administered BMMCs as well as peripheral mast cells infiltrate the brain in pathological conditions and thus exacerbate neuroinflammatory response (Silverman et al, 2000; Tanzola et al, 2003; Bennett et al, 2009; Skaper et al, 2012; Skaper et al, 2013a).…”
Section: Discussionmentioning
confidence: 99%
“…Male animals, used to exclude potential estrous cycle effects (13), were group housed under standard conditions at 21°C on a 12:12-h light-dark cycle with environmental enrichment and ad libitum access to water and food. All efforts were made to minimize animal suffering, and the number of animals used, n ϭ 6 rats/group for the MCAO study and n ϭ 5-7 rats/group for the platelet study, was based on a priori power calculations at 80% power and a significance level of 5% (52) and on previous publications (30,43,54). In all experiments, terminal anesthesia was induced and maintained by inhalation of isoflurane.…”
Section: Animalsmentioning
confidence: 99%